HUBUNGAN PENGETAHUAN TENTANG FLU BURUNG DENGAN SIKAP MASYARAKAT YANG MEMELIHARA UNGGAS DI WILAYAH MOJOGEDANG - Miftahudin, Arysyad; Kartinah, Kartinah (Jurnal Berita Ilmu Keperawatan, 2008)
Background : Avian influenza (AI) the thing which know be familier the community like avian influenza is respiration acces-duct dease couse by foult one influenza virus A. the community reluctant for report dead bird in a sadden manner because take care of bird is economics well, with community submissive where must report and beable help until belated give treatment. If made one scale knowledge and attitude about avian influenza that is between 1 to 10, the community awareness will avian influenza this level 3 scale. The community meaning regard as avian influenza virus not costitude important problem. Knowledge and attitude concerning health will influential about health behaviour included this avian influenza case. Aim. This research aim to knowing relation between knowledge this influenza with attitude the community of avian farm. Method of research. Method of this correlation Descriptive method with cross sectional approach. Data Intake use primary data in kuesioner form. This research is executed in June 2007 until March 2008 in farm Mojogedang district. The research sample is taken with Proporsionalrandom sampling technich and got 36 sample fulfilling Inklusi, data anlised by correlasi product moment from pearson test. Result. Result of research showing : (1). Level knowledge respondent of about avian influenza indicate that most respondent in this have good knowledge. (2). Attitude respondent of about avian influenza indicate that most respondent they have positif attitude serious for avian influenza. (3). Knowledge of about avian influenza have relation the thing which signifikate with attitude the community avian farm.